Assessing Liver Function in Rat Models of Acute Liver Failure Using Single-Photon Emission Computed Tomography and Cytokine Levels - Long Xie; Liqun Huang; Xueting Fang; Jinshun Zha; Yingrui Su (PLoS ONE, 2025)
Objective To evaluate liver function using dynamic hepatobiliary single-photon emission computed tomography (SPECT) in different rat models of acute liver failure. Methods Twenty-four 6–8-week-old male Sprague–Dawley rats (weight 190–200 g) were evenly divided into four groups. Acute liver failure was induced by intraperitoneal injection of D-galactosamine (D-GalN, 600 mg/kg) and lipopolysaccharide (LPS, 10 µg/kg), common bile duct ligation surgery, and removing 70% of the liver mass. The fourth group served as the control without intervention. The time-activity curves for the liver and heart were generated from dynamic SPECT scans with 99mTc-ethylene hepatobiliary iminodiacetic acid (EHIDA). Image-derived functional parameters (5-minute heart/liver index [HLI5] and 15-minute receptor index [LHL15]) were calculated. Furthermore, correlations of image-derived parameters with serum interleukin-6 (IL-6) levels, liver aspartate aminotransferase (AST) and alanine transaminase (ALT) levels, and liver mRNA expression levels of tumor necrosis factor-α (TNF-α) and chemokine ligand-10 (CXCL-10) were analyzed. Results All animals in the experimental groups exhibited varying degrees of liver damage. The SPECT images and indexes (HLI5 and LHL15) of the experimental groups significantly differed from those of the control group (P < 0.05). In the experimental groups, serum IL-6 levels and liver mRNA levels of TNF-α and CXCL-10 were significantly higher, while liver AST and ALT levels were significantly lower than those in the control group (P < 0.05). Conclusion Using SPECT with 99mTc-EHIDA, along with the calculated indexes and levels of various cytokines, presents a dependable method for assessing liver function.